60+0.3x=x

Simple and best practice solution for 60+0.3x=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 60+0.3x=x equation:


Simplifying
60 + 0.3x = x

Solving
60 + 0.3x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
60 + 0.3x + -1x = x + -1x

Combine like terms: 0.3x + -1x = -0.7x
60 + -0.7x = x + -1x

Combine like terms: x + -1x = 0
60 + -0.7x = 0

Add '-60' to each side of the equation.
60 + -60 + -0.7x = 0 + -60

Combine like terms: 60 + -60 = 0
0 + -0.7x = 0 + -60
-0.7x = 0 + -60

Combine like terms: 0 + -60 = -60
-0.7x = -60

Divide each side by '-0.7'.
x = 85.71428571

Simplifying
x = 85.71428571

See similar equations:

| 5x-8=(6m+4) | | -7/2w=5/6 | | -7/2w5/6 | | 5+y*y=36 | | -2=9/8v | | 3.00=0.45b | | x+15=3x-7 | | 13x+3-4x=3x-8 | | 1/4a=4 | | 7h-6=4h+3 | | 5p+9=3p+13 | | (3x-4)(5x+15)=0 | | -96-58=-1894 | | 3m=7(m+6) | | 11=(-2x+2)+5 | | 38x+16=54 | | 36+3x=12x | | 9w=56+w | | 2x-3x+18=-4x-4 | | 4n+65=93 | | U=48n+210+7n+7 | | 18+2x=6y | | 1x+30=2x | | Y=2/9x-7 | | 1x+54=7x | | 2=10/3z=3z-7/3 | | 1/16a^2-1/25=0 | | a=8+b | | U=6*8n+6*35+7*n+7*1 | | =6*8n+6*35+7*n+7*1 | | x^2-208=0 | | f(a)=4x^2+2x+8 |

Equations solver categories